How not to be a politician a memoir - Stewart, Rory 1973- (Penguin Press, 2023)
From a great writer-legendary for his expeditions into some of the world's most forbidding places comes a sometimes-absurdist memoir of a most remarkable journey through British politics at the breaking point
Includes index
Keywords: Stewart, Rory; Great Britain / Politics and government / 2007-; Politicians / Great Britain / Biography; Cabinet officers / Great Britain / Biography; Autobiographies